Menstruation Education as a Sign of Maturity in Children: Nursing Approach and Islamic Law Perspective - Talia Berliana Fransisca; Arlita Dwi Wahyuni Leksono; Rahma Khoirunnisa; Alya Rafeyfa Maliha; Syifa Khoirunnisa (al-Iltizam: Jurnal Pendidikan Agama Islam, 2026)
Children's limited understanding of menstruation remains a significant issue that may lead to psychological unpreparedness, inadequate hygiene practices, and limited comprehension of religious obligations during menstruation. This study aimed to explore menstrual education as a sign of maturity in children through a nursing approach and an Islamic legal perspective. A descriptive qualitative design was employed involving six informants consisting of parents, healthcare professionals, and religious scholars, conducted in various locations where the informants resided. The findings revealed that menstruation is understood as a natural biological process as well as a marker of puberty (baligh). However, the education provided remains limited and lacks comprehensiveness. Menstrual hygiene practices have been implemented, although not yet fully aligned with health standards, while understanding of menstrual pain and warning signs has begun to develop. Furthermore, menstruation is perceived as the beginning of spiritual responsibility related to religious obligations and the understanding of purification (thaharah). The study concludes that menstrual education should be delivered holistically by integrating health aspects and religious values to enhance children's physical, psychological, and spiritual preparedness. This research contributes to the achievement of Sustainable Development Goal (SDG) 3 (Good Health and Well-being) and SDG 4 (Quality Education) through the strengthening of comprehensive reproductive health education.